Salafi Movement in Greater Bandung after Reformation (1998–2025): Role and Impact on Local Social and Cultural Transformation - Amung Ahmad Syahir Muharam; Ajid Thohir (Hanifiya: Jurnal Studi Agama-Agama, 2026)
This study analyzes the development and influence of the Salafi movement in Bandung since the post-Reformation period (1998–present) through an interdisciplinary approach combining History, Sociology, and Anthropology. It traces the movement’s genealogy from a daʿwah phenomenon to a significant social force in the public sphere. Theoretically, Ralf Dahrendorf’s Conflict and Resistance Theory is used to examine tensions between Salafi groups and traditional religious authorities, highlighting how struggles over authority and influence generate polarization and local resistance rooted in cultural identity. Anthony Giddens’ Structuration Theory illuminates the duality of structure: Salafi agents employ democratic spaces and information technology to spread their ideology, while their actions gradually reshape norms, religious practices, and lifestyles in Bandung society. The research employs a qualitative field case study. Historical data were gathered through archival research and oral histories to map infiltration phases; sociological and anthropological data were collected via participant observation and in-depth interviews with movement leaders, local communities, and academics. Findings indicate that the Salafi movement in Bandung is not monolithic but adaptive to societal dynamics. It has produced social transformation, including shifts in religious consumption, changes in lifestyle, and redefinitions of grassroots social relations. While triggering horizontal conflict (Dahrendorf), the movement also demonstrates agency (Giddens) by creating new subcultures that now constitute part of Bandung’s sociological diversity in the modern era.